Improving Student Motivation and Self-Regulation in Science and Mathematics Classes: Examining the Impact of the Learning Environment - Burdakova, Yulia (Curtin University, 2018)
The overarching aim of this study was to investigate malleable learning environment factors that could be changed to enhance students’ motivation in mathematics and science classes. This mixed-methods study involved the collection of: quantitative data (N=19 classes with 351 students) using surveys to assess students’ perceptions of the learning environment and student motivation; and qualitative information (N=56 students) using observations and interviews. The results provide important information about how to create motivation-driven classroom environments.